Price and QoS differentiation in all-IP networks. (2016) - Knieps, Günter; Stocker, Volker
In this paper, the evolutionary transition towards all-IP networks is described and the necessity for entrepreneurial QoS differentiations is shown. Challenges resulting from the full migration to all-IP service provision are specified and the relevance of traffic services endowed with either deterministic or stochastic QoS guarantees is explained. An incentive compatible price and QoS differentiation scheme for the Generalized DiffServ architecture is presented. Policy implications criticising the recent introduction of network neutrality regulations in the USA and Europe by means of a two-tiered traffic regulation are derived.